Restricted data : the history of nuclear secrecy in the United States - Wellerstein, Alex (Chicago ; London : University of Chicago Press, 2021)
"Nuclear weapons, since their conception, have been the subject of secrecy. In the months after the dropping of the atomic bombs on Hiroshima and Nagasaki, the American scientific establishment, the American government, and the American public all wrestled with what was called the "problem of secrecy," wondering not only whether secrecy was appropriate and effective as a means of controlling this new technology but also whether it was compatible with the country's core values. Out of a messy context of propaganda, confusion, spy scares, and the grave counsel of competing groups of scientists, what historian Alex Wellerstein calls a "new regime of secrecy" was put into place. It was unlike any other previous or since. Nuclear secrets were given their own unique legal designation in American law ("restricted data"), one that operates differently than all other forms of national security classification and exists to this day. Drawing on massive amounts of declassified files, including records released by the government for the first time at the author's request, Restricted Data is a narrative account of nuclear secrecy and the tensions and uncertainty that built as the Cold War continued. In the US, both science and democracy are pitted against nuclear secrecy, and this makes its history uniquely compelling and timely"--
Includes bibliographical references and index.
Keywords: Nuclear weapons information, American -- Access control; Defense information, Classified -- United States